2021
DOI: 10.1111/acps.13361
|View full text |Cite
|
Sign up to set email alerts
|

Clozapine levels as a predictor for therapeutic response: A systematic review and meta‐analysis

Abstract: Objectives Clozapine levels may be a more useful predictor of therapeutic response than the dose, given the variability in clozapine metabolism between individuals. We therefore systematically reviewed and meta‐analysed the impact of clozapine levels on response and/or relapse to provide guidance on optimal clozapine levels. Methods We systematically searched PubMed, PsycInfo and Embase for studies exploring clozapine levels and response and/or relapse. Our primary meta‐analysis was rates of response above and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…Exploring our results further via sensitivity analyses, we saw little change in our schizophrenia PRS association by restricting the sample to only individuals of European genetic ancestry (n=2577; β= 11.46, [95% CI: 3.169-19.75], P = 0.007), and established that this result is specific to schizophrenia genetic liability by assessing a wider range of psychiatric, cognitive and personality PRS, none of which were significantly associated with clozapine doses (Supplementary Figure 2). We also confirmed that our main detected effects were still consistent and significant when restricting our dataset to observations at clozapine plasma concentration thresholds investigated in previous research on therapeutic response to the drug (20), either between 350-600 ng/L (n= 1089; β= 14.952, [95% CI: 3.167-26.737], P= 0.0131) or above (n= 1283; β= 17.258, [95% CI: 5.823-28.692], P= 0.0031).…”
Section: Primary Analysis: Association Of the Schizophrenia Prs And T...supporting
confidence: 87%
See 2 more Smart Citations
“…Exploring our results further via sensitivity analyses, we saw little change in our schizophrenia PRS association by restricting the sample to only individuals of European genetic ancestry (n=2577; β= 11.46, [95% CI: 3.169-19.75], P = 0.007), and established that this result is specific to schizophrenia genetic liability by assessing a wider range of psychiatric, cognitive and personality PRS, none of which were significantly associated with clozapine doses (Supplementary Figure 2). We also confirmed that our main detected effects were still consistent and significant when restricting our dataset to observations at clozapine plasma concentration thresholds investigated in previous research on therapeutic response to the drug (20), either between 350-600 ng/L (n= 1089; β= 14.952, [95% CI: 3.167-26.737], P= 0.0131) or above (n= 1283; β= 17.258, [95% CI: 5.823-28.692], P= 0.0031).…”
Section: Primary Analysis: Association Of the Schizophrenia Prs And T...supporting
confidence: 87%
“…We hypothesized that, given official prescription guidelines suggesting that once in the therapeutic dose range, doses should only be increased in case of non-response to the treatment, it is reasonable to postulate that higher dosing could be a proxy phenotype for poorer treatment response in the absence of adverse effects. Although this hypothesis cannot be formally tested in our data, previous studies have suggested that individuals requiring higher doses of clozapine could be an indicator of poor treatment response (20). In any case, our results show that individuals with a high schizophrenia PRS are more likely to be prescribed a high clozapine dose.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Serum drug levels are affected by age, medical conditions, genetics, drug-drug interactions, and pharmacokinetic variability; all can differ immensely between patients and during the patient’s life course. 7 Clozapine blood levels are correlated with clinical outcome: response is associated with blood levels above 350 ng/ml, 9 , 10 whereas levels higher than 600 ng/ml might be associated with increased risk to develop side effects. 10 Yet, measuring clozapine levels is complicated and often avoided.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Clozapine blood levels are correlated with clinical outcome: response is associated with blood levels above 350 ng/ml, 9 , 10 whereas levels higher than 600 ng/ml might be associated with increased risk to develop side effects. 10 Yet, measuring clozapine levels is complicated and often avoided. The current available customary analytic method of liquid chromatography tandem mass spectrometry (LC-MS/MS) requires transportation to a special lab and a multistep analysis process that may take several days.…”
Section: Introductionmentioning
confidence: 99%